2022
DOI: 10.1097/md.0000000000032152
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to vaccination against SARS-CoV-2 in patients undergoing dialysis

Abstract: Patients undergoing maintenance dialysis have a higher mortality rate associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and response rates to vaccination against SARS-CoV-2 vary from 29.6% to 96.4% in such patients. This study aimed to assess the immunogenicity of SARS-CoV-2 vaccination in Korean patients undergoing dialysis. We enrolled 70 SARS-CoV-2-vaccinated patients undergoing dialysis, with 11 healthcare workers serving as healthy control subjects. Thirty-two patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, this result differs from those of previous studies. Several studies [16][17][18][19] showed that the third dose of vaccine substantially increased antibody levels in patients receiving maintenance dialysis, and its effect was particularly noticeable in those with a lower response to the previous 2 doses of vaccine. Precisely pinpointing the reasons for the disparity between our findings and those of prior studies presents a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result differs from those of previous studies. Several studies [16][17][18][19] showed that the third dose of vaccine substantially increased antibody levels in patients receiving maintenance dialysis, and its effect was particularly noticeable in those with a lower response to the previous 2 doses of vaccine. Precisely pinpointing the reasons for the disparity between our findings and those of prior studies presents a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We compared how the antibody responses of patients undergoing HD differ according to the third vaccination dose and the antibody responses of patients undergoing HD with those of the healthy population. Since COVID- 19 is not yet over, we believe this study can help plan future vaccine administration strategies in patients undergoing HD.…”
Section: Introductionmentioning
confidence: 99%